The Effect of Transformational Leadership Towards Work Engagement: The Variable Meaning Of Work as a Mediation at the Secretariat Region of East Java Province - Praptini Yulianti; Dita Ayu Permatasari (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to see the effect of transformational leadership on work engagement with the meaning of work as a mediating variable at the Regional Secretariat of East Java Province. The population in this study were all employees with civil servant status in the existing bureaus at the Regional Secretariat of East Java Province, a total of 300 people. Sampling in this study used Slovin’s formula therefore the results obtained were 81 people. The measurement technique uses SEM-PLS ( Structural Equation Modelling-Partial Least Square on the software Smart PLS. The results of this study indicate that transformational leadership has a positive effect but not a significant effect on work engagement and the meaning of work can mediate the relationship between transformational leadership and work engagements. The mediation behavior finding in this meaning of work is full mediation, which means the independent variable is not able to significantly influence the dependent variable without going through the mediator variable, transformational leadership is unable to significantly influence the work engagements. Variable mediating behavior meaning of work strengthen influence transformational leadership to work engagement.